Anterior uveitis onset after bnt162b2 vaccination: is this just a coincidence? - Renisi, Giulia; Lombardi, Andrea; Stanzione, Massimo; Invernizzi, Alessandro; Bandera, Alessandra; Gori, Andrea (International journal of infectious diseases, 2021)
•Uveitis is a vision-threatening inflammation and can be elicited by vaccination.•We describe a case of uveitis that occurred after BNT162b2 COVID-19 vaccination.•After treatment with topical steroids, visual acuity was completely restored. Uveitis is a vision-threatening inflammation and is considered an ophthalmic emergency. It generally arises as a result of autoimmune conditions, infections, or ocular trauma, but it may also occur as an isolated disorder. Over the past decades, several cases of vaccine-associated uveitis have been described, with the hepatitis B virus vaccine being the leading cause. A case of anterior uveitis in a 23-year-old male, with onset 14 days after the second dose of BNT162b2 COVID-19 vaccine, is reported here. Initial symptoms were pain, photophobia, and red eye. Ocular examination showed pericheratic and conjunctival hyperaemia, posterior synechiae, and anterior chamber cells ± keratic precipitates in the lower quadrants. The posterior segment did not show any alteration, and optical coherence tomography ruled out the presence of cystoid macular oedema. After a 10-day treatment course of topical steroids and cycloplegic eye drops, the ocular inflammatory signs disappeared and visual acuity was completely restored. Even if causality remains presumed, a warning should be given to physicians about the possibility of eye inflammation following SARS-CoV-2 vaccination.